The Role of Cloud Computing in Education - Mohammed Abdullah Saeed Al-Amri (International Journal of Computers and Informatics, 2025)
This study aimed to analyze the role of cloud computing in the education sector, as this technology brings positive transformations by making education more accessible, effective, and efficient. However, educational institutions face challenges related to security, privacy, cost, and technical infrastructure, highlighting the need for an analytical study to examine the benefits and challenges of implementing cloud computing in this sector. The study adopted a descriptive analytical approach by reviewing and analyzing intellectual production related to cloud computing in education without collecting field data. The research procedures involved gathering, classifying, and analyzing previous studies, scientific reports, and relevant statistics to derive key trends and insights. The findings revealed that cloud computing offers numerous benefits, including reducing operational costs, increasing flexibility and scalability, and enhancing data security. Additionally, cloud computing supports digital transformation in education, improves academic data management, and provides an integrated learning environment powered by artificial intelligence. However, institutions face challenges such as dependence on internet connectivity, privacy concerns, and the need to select appropriate cloud models. The study recommended a well-planned transition to cloud computing by carefully selecting suitable models, strengthening technical infrastructure, and ensuring data security. It also emphasized the importance of providing comprehensive training for teachers and students and conducting periodic assessments to measure the effectiveness of cloud computing in improving the educational process.